Latent tuberculosis infection one year after exposure among hospital laboratory workers - Ruamtham, Narathip; Chaiear, Naesinee; Krisorn, Phanumas; Faksri, Kiatichai; Chanpho, Patimaporn (Asia-Pacific Journal of Science and Technology, 2023)
Health workers are at high risk of tuberculosis (TB) infection through occupational exposure to tuberculosis, and medical laboratory personnel are a high-risk group for getting TB at work. The infection can be caused by their work process and/or be contracted from co-workers. Latent tuberculosis infection (LTBI) detection and controls are thus needed to prevent the spread of TB in the workplace. The current study aimed to determine the proportion and characteristics of laboratory personnel infected with tuberculosis. All medical laboratory workers 75 individuals employed in the medical laboratories in a hospital in northeastern Thailand with high or medium prioritized contact with TB index cases in the workplace between September 2019 to October 2020 were included in the study. Post-exposure TB surveillance data were obtained from the Occupational Health and Safety Office, and laboratory work processes and work environment data were collected through workflow studies and interviews. After a one-year follow-up, the proportion of LTBI among medical laboratory workers was 13.3% (ten persons). The bivariate conditional logistic regression analysis showed that older age (>55 years) (odds ratios (OR) 6.57, 95% confidence intervals (CI): 1.43,29.93, p 0.063), and workers with high-prioritized contact (OR 3.986, 95%CI 1.595, 8.974, p 0.030) had a statistically significant association with the occurrence of LTBI. LTBI in the workplace among medical laboratory workers was probably caused by prolonged, cumulative, close contact with infected co-workers in daily life activities rather than work-related procedures.